1990
DOI: 10.1084/jem.172.6.1609
|View full text |Cite
|
Sign up to set email alerts
|

Human keratinocytes are a source for tumor necrosis factor alpha: evidence for synthesis and release upon stimulation with endotoxin or ultraviolet light.

Abstract: SummaryTumor necrosis factor a (TNF-a), in addition to being cytotoxic for certain tumor cells, has turned out as a multifunctional cytokine that is involved in the regulation of immunity and inflammation. Since human keratinocytes have been demonstrated to be a potent source of various cytokines, it was investigated whether epidermal cells synthesize and release TNF-m Supernatants derived from normal human keratinocytes (HNK) and human epidermoid carcinoma cell lines (KB, A431) were tested both in a TNF-a-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
333
2
8

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 658 publications
(358 citation statements)
references
References 30 publications
15
333
2
8
Order By: Relevance
“…We have recently shown that urocanic acid, which has been implicated as the photoreceptor within the skin for UV radiation and mediator of some immune suppressive effects of UVB, is not able to down-modulate CR expression in human neutrophils in vitro [36]. It is well established that UVB-irradiated keratinocytes secrete a wide variety of modulatory cytokines, of which tumor necrosis factor ␣ and interleukin-10 are perhaps the most important [37,38]. It is known that tumor necrosis factor ␣ is a stimulatory cytokine for phagocytes, capable of up-regulating, for instance, leukocyte CR3 [39].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that urocanic acid, which has been implicated as the photoreceptor within the skin for UV radiation and mediator of some immune suppressive effects of UVB, is not able to down-modulate CR expression in human neutrophils in vitro [36]. It is well established that UVB-irradiated keratinocytes secrete a wide variety of modulatory cytokines, of which tumor necrosis factor ␣ and interleukin-10 are perhaps the most important [37,38]. It is known that tumor necrosis factor ␣ is a stimulatory cytokine for phagocytes, capable of up-regulating, for instance, leukocyte CR3 [39].…”
Section: Discussionmentioning
confidence: 99%
“…Lewis et al (15) found a large release of TNFa from keratinocytes in vitro in response to irritants. TNFa will also be released from keratinocytes in response to lipopolysaccharides (16). TNFa is proinflammatory and activates T cells, macrophages and granulocytes, inducing altered expression of cellular adhesion molecules and release of cytokines (17).…”
Section: Tnfa Irritancy and Allergymentioning
confidence: 99%
“…Following U.V.-induced skin inflammation in mice, keratinocytes secrete increased levels of ET-1 (Ahn et al, 1998). Keratinocytes also produce pro-inflammatory cytokines such as TNF-α, TGF-β and IL-1β that in turn, can trigger ET-1 synthesis and secretion from endothelial and epithelial cells (Ahn et al, 1998;Ansel et al, 1990;Kock et al, 1990). Human polymorphonuclear neutrophils (PMNs) also synthesize ET-1, providing an additional source to accompany inflammatory cytokine release in the early stages of inflammation.…”
Section: Discussionmentioning
confidence: 99%